Liberal education, civic education, and the Canadian regime : past principles and present challenges - Livingstone, David W., 1967- (McGill-Queen's University Press, 2015)
"Liberal Education, Civic Education, and the Canadian Regime asks what is the place of a liberal education--that is, studying the great books and Canada's political and philosophy history, as in the tradition of the liberal arts--in the education and development of the idea of citizenship in the Canadian public (what the editor, Livingstone, and his contributors call "civic education"). The liberal education stands in contract to the transferable job skills of a vocational training that can further technological, economic, and social progress. In the introduction, Livingstone considers whether studying Canada's early documents and tradition can recover and resuscitate the debates that occurred at the time of the country's founding and also resurface to shed light on contemporary issues."--